PERAN PASAR TRADISIONAL BANTAENG DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KOTA BANTAENG KAB. BANTAENG - Fadilah T, Annisah Nurul (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the role of traditional markets in improving the welfare of the community in Bantaeng City. Using a descriptive qualitative research approach, this study found that the role of Bantaeng traditional markets in improving the welfare of the community has been successful, although not optimal. The results of the study indicate that Bantaeng traditional markets have helped lower-middle-class communities meet their economic needs by providing easy access and affordable prices for various types of goods and services. In addition, Bantaeng traditional markets have also become important centers of economic activity for the surrounding community, thereby increasing their income and welfare. However, there are still several challenges that need to be overcome to increase the role of traditional markets in improving the welfare of the community, such as improving market infrastructure, increasing security, and market promotion. Therefore, the government must pay more attention to traditional markets so that their management can be improved, especially in terms of building adequate stalls, parking areas, and market security. Thus, the results of the study indicate that Bantaeng Traditional Markets play a role in improving the welfare of the community in Bantaeng Regency.